The role of Unesco in defining Guidelines for Non-Formal Education (Research, Society and Development, 2020)
The objective of research was to present UNESCO's proposals for the field of non-formal education in the international arena as well as the organization's guidelines for recognition, validation and certification of educational initiatives of this nature. As a way of understanding the concept of non-formal education and its implications in the process of economic and human development, the theoretical foundation proposed by Coombs, Delors, Faure and Gohn was adopted. Thus, the research was classified as qualitative with a focus on historical research, being analyzed technical documents of the organization were analyzed that describe the principle of understanding and evaluation of the field in question, stating the importance of it in the global socio-economic scenario and the necessary creation of a guiding instrument and certifying the actions of the teaching-learning process. It begins with the description of the field of non-formal education according to UNESCO, through the organization of specific actions in the area and due purposeful ratings, ending with the directives of recognition, validation and certification (RVC) of non-education formal as an analytical assessment tool for governments in the determination of educational policies. In conclusion, UNESCO tries to provide a policy equalizer instrument in the field of non-formal education aligned with a concept to adapt to the globalized production system from the dynamic brought by the education principle throughout life.